Revisiting Polymorphic Diversity of Aminoglycoside N-Acetyltransferase AAC(6′)-Ib Based on Bacterial Genomes of Human, Animal, and Environmental Origins - Kim, Dae-Wi; Thawng, Cung N.; Lee, Kihyun; Cha, Chang-Jun (Frontiers in Microbiology, 2018)
The prevalence of aac(6′)-Ib variants has been demonstrated in numerous epidemiological studies. We revisited the polymorphic diversity of aminoglycoside 6′-N-acetyltransferase gene (aac(6′)-Ib) in the bacterial genome databases based on One Health perspectives. Aac(6′)-Ib was searched against bacterial complete and draft genome databases of NCBI. Based on the major polymorphic residues 102, 117, and 179, taxonomy, ecology, and temporal emergence of bacterial isolates harboring variants of aac(6′)-Ib gene were evaluated using whole-genome sequences available in the databases. A total of 3,964 aac(6′)-Ib sequences were found to be present in the genomes of 34 bacterial genera, mostly found in Gammaproteobacteria. Among these, aac(6′)-Ib-cr variant, known to confer fluoroquinolone resistance, were increasingly detected in bacterial genomes and most abundant in the genera Klebsiella and Escherichia, thereby suggesting that these genera were the major reservoirs of the plasmid-mediated fluoroquinolone resistance (PMQR) determinants. The proportions of the cr variant were higher in animal and environmental isolates than in human isolates, among which the variant was dominant (>50%) in the genomes of intestinal, rectal, and fecal origins. In addition, our study suggested that the prevalence of cr variant was associated with the occurrence of a variant with the mutation L117 (IbL). An integrated surveillance system for antimicrobial resistance in human, animal, and environmental sectors, based on whole-genome sequencing, would provide a better insight into the evolution, ecology, and epidemiology of antimicrobial-resistant bacteria.